Combined baseline and one-month changes in big endothelin-1 and brain natriuretic peptide plasma concentrations predict clinical outcomes in patients with left ventricular dysfunction after acute myocardial infarction: Insights from the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) study. (15th August 2017) - Olivier, A; Girerd, N; Michel, JB; Ketelslegers, JM; Fay, R; Vincent, J; Bramlage, P; Pitt, B; Zannad, F; Rossignol, P; ,
Abstract: Objective: Increased levels of neuro-hormonal biomarkers predict poor prognosis in patients with acute myocardial infarction (AMI) complicated by left ventricular systolic dysfunction (LVSD). The predictive value of repeated (one-month interval) brain natriuretic peptides (BNP) and big-endothelin 1 (BigET-1) measurements were investigated in patients with LVSD after AMI. Methods: In a sub-study of the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS trial), BNP and BigET-1 were measured at baseline and at 1 month in 476 patients. Results: When included in the same Cox regression model, baseline BNP ( p  = 0.0003) and BigET-1 ( p  = 0.026) as well as the relative changes (after 1 month) from baseline in BNP ( p  = 0.049) and BigET-1 ( p  = 0.045) were predictive of the composite of cardiovascular death or hospitalization for worsening heart failure. Adding baseline and changes in BigET-1 to baseline and changes in BNP led to a significant increase in prognostic reclassification as assessed by integrated discrimination improvement index (5.0%, p  = 0.01 for the primary endpoint). Conclusions: Both increased baseline and changes after one month in BigET-1 concentrations were shown to be associated with adverse clinical outcomes, independently from BNP baseline levels and one month changes, in patients after recent AMI complicated with LVSD. This novel result may be of clinical interest since such combined biomarker assessment could improve risk stratification and open new avenues for biomarker-guided targeted therapies. Key messages: In the present study, we report for the first time in a population of patients with reduced LVEF after AMI and signs or symptoms of congestive HF, that increased baseline values of BNP and BigET-1 as well as a further rise of these markers over the first month after AMI, were independently predictive of future cardiovascular events. This approach may therefore be of clinical interest with the potential of improving risk stratification after AMI with reduced LVEF while further opening new avenues for biomarker-guided targeted therapies.